Non-linear Numerical Modeling of Partially Pre-stressed Beam-column Sub-assemblages Made of Reactive Powder Concrete - Bambang Budiono; Siti Aisyah Nurjannah; Iswandi Imran (Journal of Engineering and Technological Sciences, 2019)
Three partially pre-stressed interior beam-column sub-assemblages (SI) and two partially pre-stressed exterior beam-column sub-assemblages (SE) made of reactive powder concrete as test specimens were numerically modeled using a finite element program. The objective of this study was to investigate the behavior of the SI and SE numerical models. The numerical model inputs were: material data, details of test specimen dimensions, and test specimen reinforcements. The numerical models were subjected to the same loads as those applied experimentally. The numerical modeling results were hysteretic and backbone curves and stress distribution contours. The numerical model outputs showed good similarity with the experimental results. The stress distribution contours of the numerical models correlated with the crack patterns in the joint zone of the test specimens. The behavior of the SI numerical models differed from the SE numerical models due to various stresses on the beam plastic joints and the joint zones.